Study on Seepage Characteristics of Radial Flow in Rock Mass Based on Radius Effect. (30th January 2022) - Liu, Kaichen; Chai, Junrui; Zhang, Yao; Tian, Ying; Li, Ruiqing
Abstract : The radial fluid flow in fractures is affected by the size of the inner diameter and the position of the outer diameter, but the influence of the two factors on the flow velocity remains unclear. This study reveals the relationship through the coupled shear flow experiments and numerical simulations. Experimental results show that the fracture aperture is decreased by 0.175 mm under the unit effective stress, with the increase of 0.902 MPa in the shear stress. COMSOL is used to simulate the seepage of fractures under different inner and outer diameters. Simulation results show that the transition from nonlinear to linear flow occurs in the radial direction when the hydraulic pressure is 0.2 and 0.4 MPa, and the positions of linear flow are 42 mm and 71 mm. The effect of the fracture surface results in a stratified flow velocity when the fluid flow enters the fracture aperture. Increasing the inner diameter raises the flow rate but decreases the maximum flow velocity. The maximum velocity difference can be as much as three times when the inner diameter difference is 6 mm. The seepage width of radial flow has a nonlinear relationship with the inner and outer diameters. The growth rate of the seepage width decreases as the ratio of the outer to the inner diameter increases. The modified cubic law considering the radius effect is proposed to improve the calculation accuracy of radial flow.